Parázsló munkaerőpiac - Schwertner, János (Tér és Társadalom, 1994)
The past four years in Hungary was a period of political and economic systemic change, which dramatically transferred the labour market processes. More exactly it created a real labour market. The balance of demand and supply changed towards the supply side from the summer of 1990 in the nation, and from the end of 1990 in Southern Transdanubia. A huge number of jobs were eliminated temporarily or for ever. Thousands of employees lost jobs that had been thought to be certain before. The reasons for unemployment are various and have contributed during the past four years to the formation of unemployment of different intensities. We can summarise the reasons as follows: loss of COMECON markets reduction of the support system for agriculture impact of the recession in the developed countries narrowing of the inner market transformation of firms privatisation, new property structure transition of the geopolitical situation of Hungary. The result is the drop in the number of employees (1.3 million persons). The number of registered unemployed exceeded 700,000. This practically made unemployment a general phenomenon. In 1993, almost one million people were given unemployment benefits or payments for more than one day. Since the beginning of unemployment, a quarter of the active earners have received some form of unemployment care. Simultaneously with the significant decline in employment, the rates of the three largest employment sectors changed. In the primary sector the rate of the employment decreased from 18 to 10%, and in the secondary sector from 37% to 35%, whíle the tertiary sector realised a growth from 45% to 55%. The direction of the transition is favourable. It approaches the developed market economies, but the form and the speed of the changes are worrying. The former uniform, false labour market, broke up as a consequence of unemployment. This is because unemployment touches all parts of the country, although not in the same measure. The labour markets where the production did not weaken, where there is a demand for services, where we can encounter developed urban functions, where the entrepreneurial willingness remained, have unemployment rates that are within acceptable limits. In the Southern Transdanubian region, situated ín the South-Western part of the country, 78,000 unemployed are registered for the time being, the unemployment rate is practically the same as the national average (12.4%). In some regions of Southern Transdanubia unemployment appeared quickly, while it still can be considered low in some other areas. In Southern Transdanubia the positive and negative changes in the labour market are both present. The labour supply is activated faster than the average, but in some regions of Zala and Somogy counties serious reductions are still expected. The tourism connected with Lake Balaton, and agricultural production provide a great number of workers with seasonal employment. It is difficult to evaluate the consequences of seasonal employment yet, but it is undeniable that this will be the only chance of employment for thousands in Southern Transdanubia. There are significant regional differences in the unemployment within Hungary, which do not leave Southern Transdanubia untouched, either. These regional differences can be summarised in five groups: West-East dualism; in Hungary the unemployment of the Eastern areas is strikingly higher at all aggregational levels The socially and economically underdeveloped areas practically coincide with the areas with high unemployment During the past four years the circle of labour markets that are the most favourable and the most unfavourable for the unemployed has hardly changed Unemployment rolled through the country as a negative diffusional phenomenon from the East to the West where the neighbourhood connections were more important than was predicted The scales of unemployment is in an inverse proportion with the population size of the settlements. While the capital has a 6% unemployment, the same figure in the small villages of Southern Transdanubia is 20%. For all these reasons, in the treatment of domestc unemployment we cannot avoid the close cooperation of regional development and employment policy.